2018
DOI: 10.1016/j.jgr.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing method on the pharmacokinetics and tissue distribution of orally administered ginseng

Abstract: BackgroundThe use of different methods for the processing of ginseng can result in alterations in its medicinal properties and efficacy. White ginseng (WG), frozen ginseng (FG), and red ginseng (RG) are produced using different methods. WG, FG, and RG possess different pharmacological properties.MethodsWG, FG, and RG extracts and pure ginsenosides were administered to rats to study the pharmacokinetics and tissue distribution characteristics of the following ginsenosides—Rg1, Re, Rb1, and Rd. The concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Ginsenoside Rb1 was found to have only a single peak at about 6 h in the mean plasma concentration–time profile, which was in agreement with previously reported results (Chen et al, ; Kim, ; Wang et al, ). These previous studies have proved the poor bioavailability of ginsenosides after oral administration.…”
Section: Resultssupporting
confidence: 92%
“…Ginsenoside Rb1 was found to have only a single peak at about 6 h in the mean plasma concentration–time profile, which was in agreement with previously reported results (Chen et al, ; Kim, ; Wang et al, ). These previous studies have proved the poor bioavailability of ginsenosides after oral administration.…”
Section: Resultssupporting
confidence: 92%
“…Ginsenosides Rg1, Re, and Rh1 and R1 saponins show better bioavailability than ginsenosides Ra3, Rb1, Rd, Rg3, and Rh2 saponins. In humans, the half-lives (T1/2) of saponins are usually less than 24 hours [ [24] , [25] , [26] ]. Possible drug interactions have been reported between P. ginseng and warfarin, phenelzine, and alcohol.…”
Section: Main Bodymentioning
confidence: 99%
“…Furthermore, oral bioavailability has been reported to affect the efficacy of some drugs. It has been demonstrated that the majority of ginsenosides had low oral bioavailability, which limits their long-term efficacy and stability (Kim et al, 2014;Biswas et al, 2017;Chen et al, 2018;Jin et al, 2018). Some scholars tend to explain the factors that lead to low oral bioavailability of ginsenosides, which large molecular weight (Han et al, 2006), low water-solubility (Liu et al, 2009), poor gastrointestinal stability of ginsenosides (Artursson et al, 1993), and intestinal or hepatic first-pass effect, then leading to low oral bioavailability (Yanni, 2007).…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%